RANCANG BANGUN SISTEM KONTROL DAN MONITORING DAYA PERANGKAT ELEKTRONIK PADA SMART HOME BERBASIS IOT - Hadi, Alif Fadhlurrahman; Zainuri, Akhmad; Asmungi, Gaguk (Jurnal Mahasiswa TEUB, 2025)
The habit of leaving electrical devices running unattended can lead to electricity wastage and, in the event of a short circuit, can potentially cause fires. Electricity consumption by PLN customers in the household sector continues to increase every year, necessitating enhanced efficiency. One solution is to use IoT to monitor and control electricity usage. This research employs the design of an IoT-based smart plug capable of monitoring AC electrical variables such as voltage, current, power, frequency, and power factor, as well as controlling a relay to cut off the power supply. Testing was conducted using a multimeter and a single-phase energy meter as a benchmark for the designed prototype. Additionally, the IoT system's response time was evaluated. From testing the ZMPT101b sensor, a difference of 4.358 V was found compared to the benchmark device, while the ZMCT103c sensor showed differences of 68.4 mA, 61.7 mA, and 68.3 mA across three loads. The power differences for each load were 0.38 W, 0.74 W, and 0.07 W, respectively. Regarding energy measurement performance, a difference of 0.1 kWh across the three loads was observed compared to the benchmark device. The actuator used is a relay, which disconnects the power supply in the event of an overload. The device's current-limiting performance was demonstrated when one circuit detected an overload (>5A), causing the relay in that circuit to successfully disconnect the power supply. The IoT system implementation was carried out via a web server with a local IP, which was then connected to the internet using the ESP32 Power Monitor application on a smartphone. With ESP32 Power Monitor, users can view sensor parameter readings and control the relay status for each load.Keywords : IoT, smart plug, power monitoring, energy efficiency, remote control